2007 25th International Conference on Computer Design 2007
DOI: 10.1109/iccd.2007.4601950
|View full text |Cite
|
Sign up to set email alerts
|

SCAFFI: An intrachip FPGA asynchronous interface based on hard macros

Abstract: Building fully synchronous VLSI circuits is becoming less viable as circuit geometries evolve. However, before the adoption of purely asynchronous strategies in VLSI design, globally asynchronous, locally synchronous (GALS) design approaches should take over. The design of circuits using complex field programmable components like state of the art FPGAs follows this same trend. In GALS design, a critical step is the definition of asynchronous interfaces between synchronous regions. This paper proposes SCAFFI, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 13 publications
0
17
0
Order By: Relevance
“…In their results, they reported a significant increase in maternal BP and HR and in fetal HR only when 50% of CVM was used in the exercises involving the back and leg extension dynamometer. The same difference was not observed with the manual grip dynamometer, and it was concluded that the size of the recruited muscle mass had more of a cardiovascular impact than the intensity of the contraction [5].…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…In their results, they reported a significant increase in maternal BP and HR and in fetal HR only when 50% of CVM was used in the exercises involving the back and leg extension dynamometer. The same difference was not observed with the manual grip dynamometer, and it was concluded that the size of the recruited muscle mass had more of a cardiovascular impact than the intensity of the contraction [5].…”
Section: Discussionmentioning
confidence: 73%
“…This modality is rarely tested on pregnant women because it increases maternal blood pressure and can subsequently affect placental circulation [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the instantiation of hard macros guarantees that all instances of a module present identical and predictable delay characteristics. This allows implementing asynchronous circuits on FPGA as demonstrated for example by Pontes et al in [16].…”
Section: Implementation On Fpgamentioning
confidence: 99%
“…18. The strategy proposed for critical timing paths is to use try and error for the routing and then compose a physical hard macro to¯x the timing.…”
Section: Proposed Implementation Strategymentioning
confidence: 99%